ANALISIS HUBUNGAN BAURAN PEMASARAN 7P TERHADAP KEPUTUSAN PEMBELIAN KATERING SEHAT BERDASARKAN INDIKATOR ASPEK KEPUASAN, LOYALITAS, SERTA HUBUNGAN PASCA PEMBELIAN PERIODE SEBELUM DAN SELAMA PANDEMI - Wilandari, Angestika; Windasari, Vicky (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Basically, consumer purchasing decisions can be influenced by the marketing mix, namely the 7Ps (product, price, process, place, promotion, people, and physical evidence). This study examines how the 7P marketing mix variables affect healthy catering purchasing decisions. Purchasing decisions in this study use indicators of satisfaction, loyalty, and post-purchase relationships. This research is quantitative with data collection methods through questionnaires and secondary data collection. The population in this study is unknown, so in determining the number of samples using the Isaac & Michael table for the population that cannot be determined. The sampling technique is non-probability sampling using incidental sampling method. The data analysis technique starts from the reliability and validity test, the classical assumption test, the partial t test, the F simultaneous test, and the coefficient of determination test. The results showed that in the pre-pandemic period the independent variable in the form of the 7P marketing mix other than product and location had a significant positive effect on purchasing decisions. The results for the second model show that product, price, and physical evidence variables have a significant effect on healthy catering purchasing decisions during the pandemic